Diagnostic features, management and prognosis of type 2 myocardial infarction compared to type 1 myocardial infarction: a systematic review and meta-analysis - Kyle White; Ian Scott; Mansey Kinarivala (BMJ Open)
Importance Distinguishing type 2 (T2MI) from type 1 myocardial infarction (T1MI) in clinical practice can be difficult, and the management and prognosis for T2MI remain uncertain.Objective To compare precipitating factors, risk factors, investigations, management and outcomes for T2MI and T1MI.Data sources Medline and Embase databases as well as reference list of recent articles were searched January 2009 to December 2020 for term ‘type 2 myocardial infarction’.Study selection Studies were included if they used a universal definition of MI and reported quantitative data on at least one variable of interest.Data extraction and synthesis Data were pooled using random-effect meta-analysis. Risk of bias was assessed using Newcastle-Ottawa quality assessment tool. Preferred Reporting Items for Systematic Reviews and Meta-analyses guidelines were followed. All review stages were conducted by two reviewers.Main outcomes and measures Risk factors, presenting symptoms, cardiac investigations such as troponin and angiogram, management and outcomes such as mortality.Results 40 cohort studies comprising 98 930 patients with T1MI and 13 803 patients with T2MI were included. Compared with T1MI, patients with T2MI were: more likely to have pre-existing chronic kidney disease (OR 1.87; 95% CI 1.53 to 2.28) and chronic heart failure (OR 2.35; 95% CI 1.82 to 3.03), less likely to present with typical cardiac symptoms of chest pain (OR 0.19; 95% CI 0.13 to 0.26) and more likely to present with dyspnoea (OR 2.64; 95% CI 1.86 to 3.74); more likely to demonstrate non-specific ST-T wave changes on ECG (OR 2.62; 95% CI 1.81 to 3.79) and less likely to show ST elevation (OR 0.22; 95% CI 0.17 to 0.28); less likely to undergo coronary angiography (OR 0.09; 95% CI 0.06 to 0.12) and percutaneous coronary intervention (OR 0.06; 95% CI 0.04 to 0.10) or receive cardioprotective medications, such as statins (OR 0.25; 95% CI 0.16 to 0.38) and beta-blockers (OR 0.45; 95% CI 0.33 to 0.63). T2MI had greater risk of all cause 1-year mortality (OR 3.11; 95% CI 1.91 to 5.08), with no differences in short-term mortality (OR 1.34; 95% CI 0.63 to 2.85).Conclusion and relevance This review has identified clinical, management and survival differences between T2MI and T1MI with greater precision and scope than previously reported. Differential use of coronary revascularisation and cardioprotective medications highlight ongoing uncertainty of their utility in T2MI compared with T1MI.